Analisis perhitungan harga pokok produksi air sebagai dasar penetapan harga jual air pada PDAM Tirta Betuah Kabupaten Banyuasin - Hendri, Edduar; Oktariansyah, Oktariansyah; Keren, Keren Hapukh Hutagaol (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
Production costs are the costs that make up the cost of production and are used as the basis for setting the selling price. To calculate the cost of production, the analytical tool used in this study is the full costing method. The purpose of this research is to compare which method is more efficient to be used/applied by the management of PDAM Tirta Betuah, Banyuasin Regency. PDAM Tirta Betuah, Banyuasin Regency uses the tariff set by the Banyuasin Regency government in calculating the basic price/base price of water products. In this study the method used is descriptive qualitative method, using interview data collection techniques. The results of this study indicate that the cost of production in 2019, 2020 and 2021 at PDAM Tirta Betuah Banyuasin Regency is Rp.4,304.46,-/M3 Rp.5,223.88,-/M3 and Rp.4,943.68,-/M3 . In calculating the selling price/tariff for water, PDAM Tirta Betuah, Banyuasin Regency, uses a basic tariff of Rp. 3,000,- /M3 for household customers. It can be seen that the cost of production is above the selling price of water. Thus, the selling price cannot fully cover operating expenses, which means the company will suffer losses in 2019, 2020 and 2021. In order to keep the costs incurred not too high, the company must reduce the high level of water leakage, so that all the water produced can be distributed and sold, then the company's profits will increase.